The Use Of Anime And Videogames As Motivational Strategies To Enhance Writing Skills In The Efl Adolescent Population In Colombia: Zankyou No Terror: From Fiction To Reality (2018)
Over the years, anime has been known as a visual reproduction that addresses issues and elements of the society. This animation alternative is based on life values and vivid lessons that are broadcasted to new generations. Likewise, the use of videogames can be a possibility to increase the capacity of different cognitive processes such as memory, critical thinking and learning.